Upaya Mengenal Pencegahan Dan Pemberantasan Tindak Pidana Pencucian Uang - Muhamad Ade Bazar Septiana; Aulia Nurdin; Asmak Ul Hosnah (Perkara : Jurnal Ilmu Hukum dan Politik, 2024)
Prevention is the process of preventing or holding back something from happening. It is possible that the eradication efforts carried out before the violation were procedures to eliminate the crime of money laundering so that criminal acts would not occur which would result in state losses. Money laundering is an attempt to hide or disguise the source of money obtained from criminal acts and then converted into money that appears to come from legitimate actions. Therefore, it is not surprising that more complex crimes are evolving into more sophisticated types as technology and science advances. Because of this, laws to overcome it are difficult to create, and criminal law itself is difficult to cover crimes such as corruption that use sophisticated tools such as telephones and computers. This type of crime also occurs in banking institutions. Often, the perpetrators are the bank administrators themselves or collaborate with other parties who are not members of the bank, so that other people do not know about it or find it difficult to understand it.